Pacific finance sector brief Fiji. (Metro Manila, Philippines Asian Development Bank, 2019)
Fiji has six commercial banks, of which five are foreign owned. The finance sector also features insurance companies, credit institutions, foreign exchange dealers, a provident fund, and the Fiji Development Bank. The country is one of only two Pacific developing member countries with a stock exchange. The Reserve Bank of Fiji is the central monetary authority and primary regulator of financial institutions. Fijis finance sector is expanding, with private sector credit growing consistently. Access to finance is limited for much of the population and the government is undertaking reforms to address this issue.
Keywords: Finance -- Fiji; Industrial policy; Electronic books